PENERAPAN STRATEGI YANG KOKOH DALAM MENINGKATKAN MUTU PENDIDIKAN - Hesti Kusumaningrum; Indriani Indriani; Syabilla Putri Atmawijaya (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Improving the quality of education is very important in improving the quality of a country's human resources. The purpose of this research is to study and analyze powerful methods to improve the quality of education. One of the common problems in education is educational inequality between different educational institutions, which leads to unequal student achievement. One of the causes that can affect the quality of education is the application of robust strategies. The results show that the implementation of robust strategies, such as the use of technology in learning, quality teacher training, relevant curriculum development and equity for learners. These can help improve the quality of education. The implication of this research is the importance of robust strategies in improving the quality of education at various levels of education from the school level to the national level. Educational institutions must also have excellent programmes and infrastructure that meets the standards for good teaching and learning continuity and there are development policies and future planning so that educational goals can be achieved.